Waspada Risiko Diabaetes Melitus Tipe 2 Melalui Skrining Gula Darah Di Yayasan Baptis Cengkareng - Sukmawati Tansil Tan; Alexander Halim Santoso; Edwin Destra; Paulus Gegana Thery Dewanto; Kresna Bambang Fajarivaldi (Compromise Journal Community Proffesional Service Journal, 2025)
Fasting blood sugar screening is a crucial step in the early detection of metabolic risks, including prediabetes and type 2 diabetes mellitus. This examination is useful for identifying at-risk individuals before clinical symptoms appear. Screening activities are carried out using the Plan–Do–Check–Act (PDCA) approach and the Point-of-Care Testing (POCT) tool. The examination was carried out on adult participants, followed by education using leaflets containing information about blood glucose control and the importance of physical activity. A total of 62 participants underwent the examination aged 23–76 years. Most participants were women (74.2%). Fasting blood sugar values ranged from 67.0 to 333.0 mg/dL with a median of 90.0 mg/dL. A total of 75.8% were in the normal category, 16.1% were pre-diabetic, and 8.1% were diabetic. Fasting blood sugar screening revealed a proportion of participants with impaired glucose regulation. These results emphasize the importance of early detection and health education, especially about physical activity which plays a role in increasing insulin sensitivity and lowering blood glucose levels. The combination of screening and education can be a preventive strategy to reduce the risk of diabetes.